Fish in the lakes, wild rice, and game in abundance : testimony on behalf of Mille Lacs Ojibwe hunting and fishing rights - McClurken, James M.; Cleland, Charles E., 1936- (Michigan State University Press, 2000)
How does one argue the Native side of the case when all historical documentation was written by non-Natives? The Mille Lacs selected six scholars to testify for them.
Keywords: Indians of North America -- Hunting -- Law and legislation -- Minnesota.; Indians of North America -- Fishing -- Law and legislation -- Minnesota.; Ojibwa Indians -- Minnesota -- Treaties.; Mille Lacs Indian Reservation (Minn.); Peuples autochtones -- Chasse -- Droit -- Minnesota.; Peuples autochtones -- Pêche -- Droit -- Minnesota.; Ojibwa -- Minnesota -- Traités.; LAW -- Administrative Law & Regulatory Practice.; Indians of North America -- Fishing -- Law and legislation; Indians of North America -- Hunting -- Law and legislation; Ojibwa Indians; Minnesota; Minnesota -- Mille Lacs Indian Reservation; Electronic books.; Treaties; Treaties.; Traités.